2019
DOI: 10.5210/fm.v24i8.10166
|View full text |Cite
|
Sign up to set email alerts
|

Across the great divide: How today's college students engage with news

Abstract: This paper reports results from a mixed-methods study about how college students engage with news when questions of credibility and “fake news” abound in the U.S. Findings are based on 5,844 online survey responses, one open-ended survey question (N=1,252), and 37 follow-up telephone interviews with students enrolled at 11 U.S. colleges and universities. More than two-thirds of respondents had received news from at least five pathways to news during the previous week; often their news came from discussions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fifth, the classroom emerged as a source of information on COVID-19. In their study of 5800 college students, Head et al [38] found that 73% of students received news updates during conversations with their professors and over 40% selected news outlets based on recommendations form faculty. The abundance of panic and concern around the pandemic meant many classroom discussions had to shift from discipline specific to current events.…”
Section: Classesmentioning
confidence: 99%
“…Fifth, the classroom emerged as a source of information on COVID-19. In their study of 5800 college students, Head et al [38] found that 73% of students received news updates during conversations with their professors and over 40% selected news outlets based on recommendations form faculty. The abundance of panic and concern around the pandemic meant many classroom discussions had to shift from discipline specific to current events.…”
Section: Classesmentioning
confidence: 99%
“…For example, college students may learn to use different academic databases or to conduct searches for library materials. There may be less focus on helping students learn to search for and evaluate information in outlets students rely on outside the classroom: just 2% of college students said they used academic databases when searching for news or information in their personal lives (Head et al, 2019). Instead, college students report that they frequently rely on open internet searches to stay informed about current events and topics that matter to them (American Press Institute, 2015; Taylor and Dalal, 2014).…”
Section: Fighting Misinformation In Collegementioning
confidence: 99%
“…The results showed that Facebook was the dominant source of the news the students accessed, followed by Snapchat, and YouTube. Through the interview, the researchers also found that the news was dominantly delivered through multiple platforms to the students' mobile alerts (Head et al, 2019).…”
Section: Literacy Practices In the New Media Ecologymentioning
confidence: 99%